COMPARISON BETWEEN DIFFERENT EARTHQUAKE MAGNITUDES DETERMINED BY CHINA SEISMOGRAPH NETWORK - Liu R.; Ren X.; Xu Z.; Yang H.; Liang J.; Ren K.; Chen Y.; Sun L. (My University, 2007)
By linear regression and orthogonal regression methods, comparisons are made between different magnitudes (local magnitude ML, surface wave magnitudes Ms and Ms7, long-period body waveQfiagnitude mB and short-period body wave magnitude mb determined by Institute of Geophysics, China Earthquake Administration, on the basis of observation data collected by China Seismograph Network between 1983 and 2004. Empirical relations between different magnitudes have been obtained. The result shows that: (1) as different magnitude scales reflect radiated energy by seismic waves within different periods, earthquake magnitudes can be described more objectively by using different scales for earthquakes of different magnitudes. When the epicentral distance is less than 1 000 km, local magnitude M L can be a preferable scale; In case M<4. 5, there is little difference between the magnitude scales; In case 4. 5<M<6. 0, m B>Ms, i. e. Ms underestimates magnitudes of such events, therefore, mB can be a better choice; In case M>6. 0, Ms>mb>mb, both mb and m b underestimate the magnitudes, so Ms is a preferable scale for determining magnitudes of such events (6. 0<M<8.5); In case M>8. 5, a saturation phenomenon appears in Ms, which cannot give an accurate reflection of the magnitudes of such large events; (2) In China, when the epicentral distance is less than 1 000 km, there is almost no difference between ML and Ms, and thus there is no need to convert between the two magnitudes in practice; (3) Although Ms and Ms are both surface wave magnitudes, Ms is in general greater than Ms7 by 0. 2 ~ 0. 3 magnitude, because different instruments and calculation formulae are used; (4) mB is almost equal to mh for earthquakes around mb4.0., but mb is larger than mb for those of mb≤ 4.5, because the periods of seismic waves used for measuring mB and mb are different though the calculation formulae are the same.
Keywords: BODY WAVE MAGNITUDE; LOCAL EARTHQUAKE MAGNITUDE; SURFACE WAVE MAGNITUDE